2015
DOI: 10.1007/s00170-015-7366-x
|View full text |Cite
|
Sign up to set email alerts
|

An automated solution for fixtureless sheet metal forming

Abstract: Manual forming of sheet metal parts through traditional panel beating is a highly skilled profession used in many industries, particularly for sample manufacturing or repair and maintenance. However, this skill is becoming gradually isolated mainly due to the high cost and lack of expertise. Nonetheless, a cost-effective and flexible approach to forming sheet metal parts could significantly assist various industries by providing a method for fast prototyping sheet metal parts. The development of a new fixturel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Another area of metalworking was also identified where we found study cases of traditional blacksmithing in which manual skill and experience with different tools, hammer, craft former, English wheel, and turning lathe for the manufacture of metal artifacts are shown (Russo B ., Cleaver, Allwood, & Loukaides, 2022) (Ilangovan, Monfared, & Jackson, 2016) (Rossi & Nicholas, 2018) (Bowen, Music, Erdinc, & Shokrani, 2021) (Russo, Cleaver, & Allwood, 2019) Similarly, we found a case study on manual skill in polishing metal parts (Kalt, Monfared, & Jackson, 2016). In addition, two particular case studies were identified on the skills for manual roughing of leather parts for shoe assembly, since it is an operation that requires great skill and experience on the part of the operator (Pedrocchi, Villagrossi, Cenat, & Tosatti , 2015).…”
Section: Robots and Automationsupporting
confidence: 65%
“…Another area of metalworking was also identified where we found study cases of traditional blacksmithing in which manual skill and experience with different tools, hammer, craft former, English wheel, and turning lathe for the manufacture of metal artifacts are shown (Russo B ., Cleaver, Allwood, & Loukaides, 2022) (Ilangovan, Monfared, & Jackson, 2016) (Rossi & Nicholas, 2018) (Bowen, Music, Erdinc, & Shokrani, 2021) (Russo, Cleaver, & Allwood, 2019) Similarly, we found a case study on manual skill in polishing metal parts (Kalt, Monfared, & Jackson, 2016). In addition, two particular case studies were identified on the skills for manual roughing of leather parts for shoe assembly, since it is an operation that requires great skill and experience on the part of the operator (Pedrocchi, Villagrossi, Cenat, & Tosatti , 2015).…”
Section: Robots and Automationsupporting
confidence: 65%
“…Lopez [16] proposed an intelligent assembly method using a 2D visual system and a learning system based on neural networks. The panel forming method proposed by Ilangovan [17] and the automatic polishing method proposed by Kalt [18] use visual and force sensors to correct the errors occurring in the manufacturing process. Mezouar et al [19] developed the external/hybrid visual force control scheme to overcome the drawbacks of the hybrid and impedance-based vision-force schemes, for which they provided an exhaustive comparative analysis.…”
Section: Review Of the Existing Solutionsmentioning
confidence: 99%
“…Lopez [13] developed an intelligent strategy to accomplish robotic fixtureless assembly using a 2D vision system and a neural network-based learning system. Vision systems and force-torque sensor were used to correct and learn error patterns occurring during various automated processes such as panel forming by Ilangovan [14] and automated polishing by Kalt [15]. Jayaweera [16,17] described a combined metrological and mathematical method to automate aircraft fuselage skin panel assembly.…”
Section: Review Of the Existing Solutionsmentioning
confidence: 99%